New fixed point theorems for orthogonal F_m-contractions in incomplete m-metric spaces - Mehmood, M.; Isik, H.; Uddin, F.; Shoaib, A. (Carpathian Mathematical Publications, 2021)
In this paper, we introduce the concept of orthogonal m-metric spaces and by using F_m-contraction in orthogonal m-metric spaces, we give the concept of orthogonal F_m-contraction (briefly, _F_m-contraction) and investigate fixed point results for such mappings. Many existing results in the literature appear to be special case of results proved in this paper. An example to support our main results is also mentioned.